The death penalty today - Bohm, Robert M. (CRC Press, 2008)
Addresses legal, empirical, political, and philosophical aspects of capital punishment. This book focuses on such topics as miscarriages of justice, including errors in conviction and possible remedies. It reviews potential causes of wrongful conviction and considers the responsibility of the state for reintegration of the wrongfully convicted.